PENGARUH PERBEDAAN KADAR KALSIUM HIDROKSIDA DAN PENAMBAHAN AIR TERHADAP KOMPOSISI KIMIA DAN KECERNAAN IN VITRO DAUN KELAPA SAWIT - Ria Anjalani; Subur Priyono Sasmito Budhi; Hari Hartadi (Buletin Peternakan, 2013)
This study was conducted to observe the effects of calcium hydroxide (Ca(OH)2) and moisture level of soakedcrude palm leaves on its chemical composition and in vitro digestibility. Level of Ca(OH)2 which used and moisture content which added for soaking process in this study were 0, 3, 6% (w/w) and 40, 50, 60% (w/w), respectively, on DM basis. This study was arranged in Complete Randomized Design using 3x3 factorial arrangements, with 3 replications. All significant results were then analysed with Duncan’s new Multiple Range Test. After treatment, oil palm leaves were placed in polyethylene plastic bag and stored for 21 days. Result showed the DM, OM, CP, CF, EE, NFE, NDF and ADF of palm leaves after treated were 37.89-59.52%, 87.83-92.96%, 8.32-9.84%, 35.91-40.63%, 5.98-7.47%, 34.66-40.06%, 64.74-75.39% and 46.56-59.32%, respectively. The IVDMD and IVOMD of palm leaves were 19.26-29.55% and 19.91-28.26%. Level of Ca(OH)2 and moisture content affected the chemical composition of palm leaves, but have no effect on its digestibility. The less effectiveness of Ca(OH)2 as a single treatment, caused by the low level of Ca(OH)2 and short time of treatment periode on palm leaves. Ca(OH)2 level of 6% and 40% moisture content was given the best results in this study. (Key words: Crude palm leaves, Ca(OH)2, Moisture content, In vitro digestibility)